Edukasi Dapat Menurunkan Kecemasan Pada Pasien Abortus Imminens - Tasya Novita; Rinda Intan Sari (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
Background: Abortion patients often experience unstable conditions which are influenced by the condition of the fetus, one of which is anxiety. Abortion and anxiety have an impact on morbidity and death in the mother and fetus, so education is needed to reduce anxiety. Objective: This study aims to analyze the effect of education on anxiety. Method: quantitative research with research design, namely quaisy experimental design with One Group Pre-test Post-test design method. Using a consecutive sampling technique with 32 respondents using the HARS measuring instrument. The statistical test used is the Wilcoxon Signed Ranks Test. Research Results: The results of the univariate analysis showed that 87.5% of the respondents were early adults and the results of the bivariate analysis showed that the pre and post values ​​for providing education on anxiety in abortion patients obtained a p-value of 0.0001 (<0.05). So it can be concluded that H0 is rejected, which means that there is a significant effect of providing education on the anxiety of patients with imminent abortion. Suggestion: It is hoped that future researchers will be able to expand the scope of research to make it more perfect and the benefits of further researchers can be developed regarding mothers' perceptions of abortion. Apart from that, you can add or combine education with other interventions.